Prioritization of predisposition genes for familial non-medullary thyroid cancer by whole-genome sequencing - Srivastava, Aayushi; Skopelitou, Diamanto; Miao, Beiping; Giagiobbe, Sara; Paramasivam, Nagarajan; Kumar, Abhishek; Diquigiovanni, Chiara; Bonora, Elena; Bandapalli, Obul Reddy; Försti, Asta; Hemminki, Kari (European journal of endocrinology, 2025)
Thyroid cancer (TC) is the most common endocrine malignancy, with 90%-95% of the cases representing non-medullary thyroid cancer (NMTC). Familial cases account only for a few of all cases and the underlying genetic causes are still poorly understood.We whole-genome sequenced affected and unaffected members of an Italian NMTC family and applied our in-house developed Familial Cancer Variant Prioritization Pipeline (FCVPPv2) which prioritized 12 coding variants. We refined this selection using the VarSome American College of Medical Genetics and Genomics (ACMG) implementation, SNAP2 predictions and further in silico scores.We prioritized 4 possibly pathogenic variants in 4 genes including Ret proto-oncogene (RET), polypeptide N-acetylgalactosaminyltransferase 10 (GALNT10), ubinuclein-1 (UBN1), and prostaglandin I2 receptor (PTGIR). The role of RET point mutations in medullary thyroid carcinoma is well established. Similarly, somatic rearrangements of RET are known in papillary TC, a specific histotype of NMTC. In contrast to RET, no germline variants in PTGIR, GALNT10, or UBN1 have been linked to the development of TC to date. However, alterations in these genes have been shown to affect pathways related to cell proliferation, apoptosis, growth, and differentiation, as well as posttranslational modification and gene regulation. A thorough review of the available literature together with computational evidence supported the interpretation of the 4 shortlisted variants as possibly disease-causing in this family.Our results implicate the first germline variant in RET in a family with NMTC as well as the first germline variants in PTGIR, GALNT10, and UBN1 in TC.